1977
DOI: 10.3382/ps.0561600
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ascorbic Acid and Vitamin E on Serum Lipids of Cockerels Fed Wesson Oil-cholesterol Diets

Abstract: The major lipid changes caused by adding 5% Wesson Oil and 1% cholesterol to cockerel diets were large increases in serum cholesterol, cholesteryl esters, and triglycerides. Lecithin and cephalin were not affected. Ascorbic acid significantly increased serum triglycerides; vitamin E significantly lowered serum cholesterol. Percentages of the saturated acids (palmitic, stearic, and arachidonic) of cockerels on the Wesson Oil-cholesterol diet decreased significantly; unsaturated linolenic and linolenic acids inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1980
1980
1991
1991

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Cholesterol and cholesteryl esters in serum were both lower when vitamin E was in the oleic plus ascorbic acid diet. These results agree with previous work done in this laboratory which showed that vitamin E significantly reduced serum cholesterol in cockerels fed a 5% Wesson oil plus 1% cholesterol diet (Klopfenstein and Clegg, 1977). More vitamin E-related changes were associated with the 10% oleic acid diet than with the palmitic acid diet.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Cholesterol and cholesteryl esters in serum were both lower when vitamin E was in the oleic plus ascorbic acid diet. These results agree with previous work done in this laboratory which showed that vitamin E significantly reduced serum cholesterol in cockerels fed a 5% Wesson oil plus 1% cholesterol diet (Klopfenstein and Clegg, 1977). More vitamin E-related changes were associated with the 10% oleic acid diet than with the palmitic acid diet.…”
Section: Resultssupporting
confidence: 94%
“…Recent studies have shown that dietary components interact and that all nutrientscarbohydrates, proteins, fiber, vitamins, and minerals, as well as lipids -can affect serum and tissue cholesterol, cholesteryl ester, and triglyceride compositions (Kritchevsky, 1978). Previous work in our laboratory has demonstrated the influence of ascorbic acid and vitamin E on serum lipid composition in cockerels fed Wesson oil and cholesterol (Klopfenstein and Clegg, 1977) and in cockerels administered diethylstilbestrol (Clegg et al, 1976).…”
Section: Introductionmentioning
confidence: 95%